A Malignant Israeli-Palestinian Conflict? A Cardiothoracic Surgeon's Perspective and Remedial Implications. Issue 1 (May 2015) - Nathanson, Michael
Abstract : A debate persists whether the Israeli-Palestinian conflict can be resolved through substantive and 'painful' compromises or that the foundational parametres of the conflict apriori deny a resolution. The nationalist Zionist agenda of mass Jewish settlement in Palestine inevitably clashed with Palestinian nationalist sentiments. Both nationalist movements saw the conflict as mutually exclusive. European imperialist designs and US political considerations at home only cemented the intractability of the conflict. As such, the conflict is akin to a human malignant process that is allowed to progress unchecked and compromises its host because those who were and are responsible to eradicate it have committed malpractice.